Gut microbiomes of bigheaded carps and hybrids provide insights into invasion: A hologenome perspective. (22nd December 2020) - Zhu, Lifeng; Zhang, Zheng; Chen, Hua; Lamer, James T.; Wang, Jun; Wei, Wenzhi; Fu, Lixia; Tang, Minghu; Wang, Chenghui; Lu, Guoqing
Abstract: Gut microbiomes play an essential role in host survival and local adaptation and thus can facilitate the invasion of host species. Biological invasions have been shown to be linked to the genetic properties of alien host species. It is thus plausible that the holobiont, the host, and its associated microbiome act as an entity to drive invasion success. The bighead carp and silver carp (bigheaded carps), invasive species that exhibit extensive hybridization in the Mississippi River Basin (MRB), provided a unique model to test the holobiont hypothesis of invasion. Here, we investigated the microbiomes of foreguts and hindguts in bigheaded carps and their reciprocal hybrids reared in aquaculture ponds using 16S amplicons and the associated gene prediction. We found an admixed pattern in the gut microbiome community in bigheaded carp hybrids. The hybrid gut microbiomes showed special characteristics such as relatively high alpha diversity in the foregut, an increasing dissimilarity between foreguts and hindguts, and a remarkable proportion of genes coding for putative enzymes related to their digestion of main food resources ( Cyanobacteria, cellulose, and chitin). The pond‐reared hybrids had advantageous features in genes coding for putative enzymes related to their diet. The above results collectively suggested that the gut microbiomes of hybrids could be beneficial to their local adaptation (e.g., food resource utilization), which might have facilitated their invasion in the MRB. The gut microbial findings, along with the intrinsic genomic features likely associated with life‐history traits revealed in our recent study, provide preliminary evidence supporting the holobiont hypothesis of invasion.